IELTS Test Training for Students in Order to Identify Students’ Perceptions and Progress in the Exam (2013)
AbstractInternational English Language Testing System (IELTS), as a standardized test is designed to assess the language ability ofstudents who need to study or work where English is the language of communication. The purpose of this study is to train students of sixth semester of Foreign Languages at the Universidad Pedagógicay Tecnológica de Colombia in IELTS test and to identify their progress in this kind of test, through applying a series of workshops. This study has a descriptive approach because it allowed us to describe and register what happened during the training. Data was collected throughoutstudents´ surveys, students´ workshops, students´ IELTS tests, and students’ reflections. This study helped students to improve and reflect about their own learning process, and it also provided the tools andinformation to take this kind of test and give  the students more confidence to assume academic challenges. Mock workshops provided students the opportunity to develop the different skills required in these kinds of tests. The activities developed during this study allowed students to improve and reflect about their own learning process and their English level.Key Words: Training, skills, international standardized test, International English Language Testing System (IELTS)